2009
DOI: 10.2215/cjn.03970609
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Stability of Parathyroid Hormone when Stored at −80°C for a Long Period

Abstract: Background and objectives: Stability of parathyroid hormone (PTH) at ؊80°C for long storage periods has never been studied. This can be of importance for the conclusions of studies where blood banks have been constituted. The study's aim was to evaluate stability of PTH when stored as serum or plasma EDTA samples at ؊80°C.Design, setting, participants & measurements: Samples were collected from 16 chronic hemodialysis patients using EDTA and gel-separator tubes. Plasma and serum were aliquoted; one aliquot was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…One study used results from plasma or serum from fresh whole blood as comparator [14], but most used results from serum or plasma which had been separated and frozen prior to analysis. For the following analysis, data have been grouped according to sample type and assay characteristics (i.e., second or third generation).…”
Section: Pico Question 1: In Human Blood Samples How Stable Is Pth Imentioning
confidence: 99%
See 2 more Smart Citations
“…One study used results from plasma or serum from fresh whole blood as comparator [14], but most used results from serum or plasma which had been separated and frozen prior to analysis. For the following analysis, data have been grouped according to sample type and assay characteristics (i.e., second or third generation).…”
Section: Pico Question 1: In Human Blood Samples How Stable Is Pth Imentioning
confidence: 99%
“…Using third generation methods, PTH was reportedly stable for 14 days in serum [43] and for 12 months in serum and plasma kept at −20°C and −80°C [30]. Observed stability may be method dependent: Cavalier et al [14,16] reported that if stored at −20°C or −80°C PTH was more stable in serum than EDTA plasma when measured using the DiaSorin Liaison method (9 vs. 2 months, respectively). In contrast, PTH was stable in both frozen serum and plasma for at least 2 years when analysed using the Roche Elecsys method.…”
Section: Stability At Other Temperaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated previously that if the primary tube is a gel type serum tube and is centrifuged without opening in the dialysis centre (assuming that the dialysis center has a centrifuge), measurement of serum PTH may be delayed by at least 18 h if the primary tube is maintained at 48C (30). Serum seems also preferable when samples have to be stored for long periods of time at -808C, such as for research studies (31).…”
Section: Choosing a Pth Assaymentioning
confidence: 99%
“…Our major concerns are mainly the definition of the "zero" point and the cut-off below which one can decide whether there is a degradation of the peptide or not. Regarding the "zero" point, most of the studies on PTH stability have used, as comparator, a sample that Brought to you by | ULg Library Authenticated Download Date | 6/8/15 11:18 AM has been immediately frozen at −20 °C [24][25][26][27][28][29][30][31] or at −80 °C [32][33][34], but few of them used an unfrozen sample, immediately assayed after centrifugation [22,[35][36][37]. The authors that used a frozen sample as T0 did that on purpose to run all the samples in one batch in order to reduce the CV, but it is unclear if this could have some consequences on the final results.…”
Section: Disadvantages Of Plasma Over Serummentioning
confidence: 99%